Pola Komunikasi di Pesantren : Studi tentang Model Komunikasi antara Kiai, Ustadz, dan Santri di Pondok Pesantren TMI Al-Amien Prenduan - Rudi Hartono (al-Balagh : Jurnal Dakwah dan Komunikasi, 2016)
Social interaction is a communication process that connects human interpersonal relationship among people. Each communication process must build a communication model that becomes an individual’s or group’s identity. Communication activities have been conducted regularly in the daily life so it needs to be observed, evaluated and corrected, especially related to its communication models.The research describes the communication process among kiai, ustadz (teachers), and santri (students) of TMI Al-Amien in 24-hour-activities, formal and non-formal activities. The method of the research is descriptive qualitative with phenomenological approach. It analyzes the communication process using the transaction, transmission, ritual, expressive, publicity and reception models.The result of analysis includes the two models of communication among kiai, ustadz (teachers), and santri (students): first, in the process of new students acceptance, Friday dialog program, and student conseling, the communication is modeled as two-direction communication dealing DeVito’s communication model, second, in Perlantasi program, the communication model used is one-direction communication dealing with Harold Dwight Lasswell’s communication model.Keyword : Social Interaction, Communication Pattern, Pondok Pesantren